Cupcake Diaries : Mia's Sweet Surprises - Coco Simon (India Simon Spotlight, 2012)
Things are slow at the cupcake shop this summer, and so when Mia$1 (Bs dad invites her on a long weekend trip to meet some of his college friends, she jumps at the chance$1 (Bespecially when she hears they have daughters her age. It turns out the girls work in an ice cream shop. Not only does Mia end up making new friends$1 (Bshe comes back with a new invention for the Cupcake Girls: an ice-cream cone cupcake!s
Keywords: Realistic Fiction -- Realistic Fiction